Educational Evaluation Management In The Productive Learning Assessment System In Vocational Schools Or Madrasah Aliyah - Hidayat, Reza; Hanif, Mamun (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Educational evaluation management in the productive learning assessment in vocational high schools or vocational madrasah aliyah is an integral part of effective vocational education. The main aim of this research is to evaluate the productive learning assessment system in the context of vocational education in vocational high schools and vocational madrasah aliyah. The method used in this research is descriptive qualitative using library sources such as books, journals, and policy documents because this method is an effective alternative for conducting research related to several vocational high schools and vocational madrasas to gain a deeper understanding of system implementation. productive assessment. The research results show that there are still several challenges in the productive assessment system, including openness in communication of assessment criteria and weights, as well as varying understanding of assessment guidelines. However, the evaluation also revealed best practices that have led to improvements in the assessment of productive learning. These results can be a basis for further improvements in the productive learning assessment system in vocational high schools and vocational madrasah aliyah, with a focus on improving the quality of vocational learning that is relevant and responsive to the demands of the job market.